Wholesale funding dry-ups - Christophe Pérignon; David Thesmar; Guillaume Vuillemey (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
We empirically explore the fragility of wholesale funding of banks, using trans-action level data on short-term, unsecured certificates of deposits in the European market. We do not observe any market-wide freeze during the 2008-2014 period. Yet, many banks suddenly experience funding dry-ups. Dry-ups predict, but do not cause, future deterioration of bank performance. Furthermore, in periods of market stress, banks with high future performance tend to increase reliance on wholesale funding. Thus, we fail to find evidence consistent with classical adverse selection models of funding market freezes. Our evidence is in line with theories highlighting heterogeneity between informed and uninformed lenders.
Keywords: G21; 330; wholesale bank funding; market freezes; asymmetric information